PERANAN PANTI ASUHAN DALAM MENUNJANG PENDIDIKAN ANAK STUDI KASUS PANTI ASUHAN PUTERA MUHAMADIYAH CABANG SRI ANTOKAN JALAN SUDIRMAN SIMPANG 4 TANGAH KECAMATAN LUBUK BASUNG KABUPATEN AGAM - Sari, Mona Mustika; Oktavia, Dian Anggraini; Erningsih, Erningsih (Pendidikan Sosiologi, 2013)
Orphanage is one of the social welfare agency responsible for providing replacement services in meeting the physical, mental and social needs of foster children ample opportunity to obtain , where appropriate their personality as well as an institution for social institutions that educate and nurture children who have social problems such as economic capacity , the lack of one of the heads of families or both , so that the family environment is no longer able to provide solutions to the problems of life that makes them feel they have no clear future . As for the problem in this research is how the role of the orphanages in supporting childrens education either formally or informally to the orphans , orphans and abandoned children , are not able to ( poor ) in the district of Agam Lubuk cone . In relation to the objectives to be achieved in this writer was to determine and describe the role of the orphanages in supporting childrens education both formally and informal.Jenis study is a qualitative research . Informants in this study is the caretaker Panti , brother foster homes and related structures in Panti Panti . The selection of informants in this study used purposive sampling techniques . Methods of data collection is done in two ways : ( 1 ) observation ( non - participant observation ) , ( 2 ) in-depth interviews , ( 3 ) documentation . Analysis of the data used by the model of interactive data analysis ( Miles and Huberman ) which includes the four stages , namely ( 1 ) data collection phase , ( 2 ) data reduction phase , ( 3 ) the stage presentation of data , ( 4 ) phase of the study concluded kesimpulan.Hasil the role of the Son of Muhammadiyah orphanage Branch Sri Antokan Lubuk cone in supporting education , both formal and informal , ( 1 ) formally : Providing a formal education to realize the highest ideals of their education kindergarten , elementary , junior high , high school and university , as well as foster children can choose which university they want . ( 2 ) Informal : Provide religious education ( spiritual ) as chanting rhythms come landfill , azan learning for primary school children , studying and preaching sermons for all ages and physical skills like holy footprint , martial arts , karate and so on as well as the language of science education Arabic and English